A Late Medieval Tannery at Tickhill, South Yorkshire. (1st January 2017) - Burgess, Andrea; Andrews, Phil
Abstract: A small excavation on the south-western periphery of Tickhill, the second most important medieval town in South Yorkshire, revealed a group of fourteenth−fifteenth-century tanning pits and an associated probable limekiln. Five tanners are recorded in the town in the late fourteenth century. Associated finds include a notable group of horn cores and a moderately diverse range of medieval pottery.